Theodor Herzl : the charismatic leader - Penslar, Derek Jonathan (Jewish lives (New Haven, Conn.), 2020)
The life of Theodor Herzl (1860-1904) was as puzzling as it was brief. How did this cosmopolitan and assimilated European Jew become the leader of the Zionist movement? How could he be both an artist and a statesman, a rationalist and an aesthete, a stern moralist yet possessed of deep, and at times dark, passions? And why did scores of thousands of Jews, many of them from traditional, observant backgrounds, embrace Herzl as their leader? Drawing on a vast body of Herzl's personal, literary, and political writings, historian Derek Penslar shows that Herzl's path to Zionism had as much to do with personal crises as it did with antisemitism. Once Herzl devoted himself to Zionism, Penslar shows, he distinguished himself as a consummate leader--possessed of indefatigable energy, organizational ability, and electrifying charisma. Herzl became a screen onto which Jews of his era could project their deepest needs and longings.--